Exogenous Nitro-Oleic Acid Treatment Inhibits Primary Root Growth by Reducing the Mitosis in the Meristem in Arabidopsis thaliana - Di Fino, Luciano M.; Cerrudo, Ignacio; Salvatore, Sonia R.; Schopfer, Francisco J.; García-Mata, Carlos; Laxalt, Ana M. (Frontiers in Plant Science, 2020)
Nitric oxide (NO) is a second messenger that regulates a broad range of physiological processes in plants. NO-derived molecules called reactive nitrogen species (RNS) can react with unsaturated fatty acids generating nitrated fatty acids (NO2-FA). NO2-FA work as signaling molecules in mammals where production and targets have been described under different stress conditions. Recently, NO2-FAs were detected in plants, however their role(s) on plant physiological processes is still poorly known. Although in this work NO2-OA has not been detected in any Arabidopsis seedling tissue, here we show that exogenous application of nitro-oleic acid (NO2-OA) inhibits Arabidopsis primary root growth; this inhibition is not likely due to nitric oxide (NO) production or impaired auxin or cytokinin root responses. Deep analyses showed that roots incubated with NO2-OA had a lower cell number in the division area. Although this NO2-FA did not affect the hormonal signaling mechanisms maintaining the stem cell niche, plants incubated with NO2-OA showed a reduction of cell division in the meristematic area. Therefore, this work shows that the exogenous application of NO2-OA inhibits mitotic processes subsequently reducing primary root growth.